2017
DOI: 10.1111/bjc.12128
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype threat and social function in opioid substitution therapy patients

Abstract: Concerns about being stereotyped can shape the social experiences of opioid substitution therapy patients. Opioid substitution therapy patients who feel negatively stereotyped experience greater social function deficits, and this relationship emerges after controlling for important clinical and mental health variables. Understanding the relationship between feeling stereotyped and social function may assist practitioners in their treatment. The study is cross-sectional, and thus, experimental or longitudinal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Collectively, blunted social abilities, stereotyped behavior, elevated anxiety and low nociceptive thresholds in morphine abstinent mice fit with clinical reports of social withdrawal, impaired cognitive flexibility and high comorbidity with anxiety disorder and depression in patients with a history of chronic opioid exposure (85)(86)(87)(88)(89)(90)(91)(92). Importantly, such negative affect, combined with conditioned effects of opioids, are considered as the two major causes of relapse in Opioid Use Disorder (93,94); they were both significantly alleviated in morphine abstinent mice under VU0155041 treatment.…”
Section: Chronic Facilitation Of Mglur4 Activity Relieves Behavioral Deficits and Dampens Behavioral Sensitization In Morphine Abstinent supporting
confidence: 60%
“…Collectively, blunted social abilities, stereotyped behavior, elevated anxiety and low nociceptive thresholds in morphine abstinent mice fit with clinical reports of social withdrawal, impaired cognitive flexibility and high comorbidity with anxiety disorder and depression in patients with a history of chronic opioid exposure (85)(86)(87)(88)(89)(90)(91)(92). Importantly, such negative affect, combined with conditioned effects of opioids, are considered as the two major causes of relapse in Opioid Use Disorder (93,94); they were both significantly alleviated in morphine abstinent mice under VU0155041 treatment.…”
Section: Chronic Facilitation Of Mglur4 Activity Relieves Behavioral Deficits and Dampens Behavioral Sensitization In Morphine Abstinent supporting
confidence: 60%
“…One reason is the discrepancy of what SF means and what measures best capture it. A study of SF in OUD [13] measured SF using The Social Functioning Scale, a measure designed to assess social adjustment in schizophrenia [61]. As mentioned previously, this study found worse SF in people on treatment for OUD, compared to matched controls.…”
Section: Strengths and Limitationssupporting
confidence: 52%
“…Despite SF being an important diagnostic feature, there is a dearth of research addressing SF in OUD. Only one trial to date, a small (n = 164) sampled Australian study, specifically examined SF in opioid users; data showed that, compared with matched controls, SF was significantly lower in patients receiving treatment for opioid use [13]. Studies involving other psychiatric disorders have linked impaired SF to greater drug use and depressive symptomatology [14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite community outreach efforts, opioid-related stigma and negative attitudes are still prevalent, and some still favor withdrawal and detox modalities despite the detrimental effects of these treatment approaches on care retention. Our stakeholder-informed evaluation con rmed that people with OUD are widely stigmatized and stereotyped (unpublished work) which can affect patient functioning [36] and whether patients seek and continue treatment [6,7]. These results emphasize a need for ongoing efforts to lower stigma, maintain open door policies for returning to treatment, and resources to maintain a patient registry and to track individuals who fall out of care, given the myriad of factors that contribute to patient success.…”
Section: Access Versus Retention In Carementioning
confidence: 80%